Adipose Tissue and Adrenal Glands: Novel Pathophysiological Mechanisms and Clinical Applications - Atil Y. Kargi; Gianluca Iacobellis (International Journal of Endocrinology)
Hormones produced by the adrenal glands and adipose tissues have important roles in normal physiology and are altered in many disease states. Obesity is associated with changes in adrenal function, including increase in adrenal medullary catecholamine output, alterations of the hypothalamic-pituitary-adrenal (HPA) axis, elevations in circulating aldosterone together with changes in adipose tissue glucocorticoid metabolism, and enhanced adipocyte mineralocorticoid receptor activity. It is unknown whether these changes in adrenal endocrine function are in part responsible for the pathogenesis of obesity and related comorbidities or represent an adaptive response. In turn, adipose tissue hormones or “adipokines” have direct effects on the adrenal glands and interact with adrenal hormones at several levels. Here we review the emerging evidence supporting the existence of “cross talk” between the adrenal gland and adipose tissue, focusing on the relevance and roles of their respective hormones in health and disease states including obesity, metabolic syndrome, and primary disorders of the adrenals.